Politics and Conditional Cash Transfer Programs: Lessons from the Philippines - Mendoza, Ronald U (Archīum Ateneo, 2016)
Poverty reduction programs are known as an effective instrument to produce electoral rewards. As such, they are generally politically appealing. But not all programs are the same from the perspective of a politician — some are more supportable than others. This article identifies the features of a conditional cash transfer (CCT) program that may be less politically appealing. First, the design and implementation features of the CCT program have control and accountability mechanisms that lower the opportunities for manipulation. Second, the cash transfer by itself does not create substantial reduction in poverty incidence in the short-term. Third, the beneficiaries’ compliance with program’s conditions may reveal the gaps in the local delivery of education and health services. Fourth, the cash assistance has the potential to weaken patron-client relationship. This article argues that even a technically sound poverty reduction program may face political resistance if it has features that are not aligned with political incentives. Rather than ignoring the political factors that are at play in the implementation of the program, they should be understood in order to improve the design of programs to make them resilient or insulated from powerful vested interests.